NASIONALISME DALAM PANDANGAN ETNIK MINORITAS DI YOGYAKARTA: - Muryanti Muryanti (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
The existence of Chinese descendants in Indonesia is obviously the parcel of well-nurtured pluralism and multiculturalism in this country. Chinese group in Indonesia remains minority among the population. However, this group reins around 70-80% Indonesian economic sectors. In terms of the feeling of nationalism, this group express it differently from other Indonesians. They obtained international recognition and yet they still acclaimed themselves as Indonesians. Plural Indonesian people have various responses and attitude towards this claim. Therefore, the main issue is not the type of nationalism, but is in the attitudes as Indonesian nation wherever and whenever it takes. This paper investigates some activities done by Chinese descendants through their organizations called INTI (Indonesian-Tionghoa Association).